Anticancer potential of AgNPs synthesized using acinetobacter sp. and curcuma aromatica against HeLa cell lines: a comparative study - Nadhe, Shradhda B.; Tawre, Madhumita S.; Agrawal, Sonia; Chopade, Balu A.; Sarkar, Dhiman; Pardesi, Karishma (Journal of Trace Elements in Medicine and Biology, 2020)
Background: Biogenic nanoparticles are gaining attention due to their low toxicity and numerous biomedical applications. Present study aimed to compare the potential anticancer activity of two biogenic silver nanoparticles (bAgNPs and pAgNPs) against human cervical cancer cell lines (HeLa). Methods: bAgNPs were synthesized using Acinetobacter sp. whereas pAgNPs were synthesized using aqueous root extract of Curcuma aromatica. Effect of these nanoparticles on HeLa cells viability was studied using MTT assay and colony formation assay. Anticancer potential was determined using fluorescence microscopy and flow cytometry studies. Bio-compatibility studies were performed against peripheral blood mononuclear cells (PBMCs). Results: Both the nanoparticles showed 50 % viability of peripheral blood mononuclear cells (PBMCs) when used at high concentration (200 mu g/mL). IC50 for bAgNPs and pAgNPs against HeLa cells were 17.4 and 14 mu g/mL respectively. Colony formation ability of Hela cells was reduced on treatment with both nanoparticles. Acridine orange and ethidium bromide staining demonstrated that bAgNPs were cytostatic whereas pAgNPs were apoptotic. JC-1 dye staining revealed that the mitochondrial membrane potential was affected on treatment with pAgNPs while it remained unchanged on bAgNPs treatment. Flow cytometry confirmed cell cycle arrest in HeLa cells on treatment with nanoparticles further leading to apoptosis in case of pAgNPs. About 77 and 58 % HeLa cells were found in subG1 phase on treatment with bAgNPs and pAgNPs respectively. bAgNPs showed cytostatic effect on HeLa cells arresting the cell growth in subG1 phase, whereas, pAgNPs triggered death of HeLa cells through mitochondrial membrane potential impairment and apoptosis. Conclusion: Overall, bAgNPs and pAgNPs could be safe and showed potential to be used as anticancer nanoantibiotics against human cervical cancer cells.
Keywords: Acinetobacter sp.; AgNPs; Anticancer; Curcuma aromatica; HeLa cells; PBMCs

Ultrasound assisted curcumin recovery from Curcuma aromatica: understanding the effect of different operating parameters - Shirsath, Sachin R.; Sable, Sunil S.; Gaikwad, Shashank G.; Gogate, Parag R. (Chemical Engineering and Processing-Process Intensification, 2021)
The present study deals with intensified extraction of curcumin from Curcuma aromatica by employing ultrasound-assisted extraction (UAE) approach also elucidating comparison with the conventional batch extraction to highlight the intensification benefits based on the usage of ultrasound. Understanding into the effect of operational parameters like type of solvent, extraction temperature, solid to solvent ratio and raw material size distribution as well as the equipment operating conditions as frequency and power on the extraction yield has been developed. Based on the results for extraction yield, the optimum conditions for UAE approach were 40 degrees C as temperature, 1:30 as solid to solvent ratio, 0.09 mm as the mean particle size, 240 W as ultrasonic power, 22 kHz as ultrasonic frequency and ethanol as the most suitable solvent. Under these optimum conditions, the highest extraction yield of 73.18% was achieved in 2 h whereas batch extraction for 14 h resulted in 52.31% yield clearly demonstrating the intensification due to ultrasound. Peleg's model was applied to explain the extraction kinetics of curcumin and the proposed model satisfactorily predicted the rates of extraction of cur cumin. Overall, UAE proved to be a better technique in terms of lesser time, lesser heating requirement and additional extraction yield.
Keywords: Cavitation; Curcuma aromatica; curcumin; Intensification; Kinetic modelling; Ultrasound assisted extraction